Falsafah Adat Minangkabau dan Hubungannya dengan Administrasi Negara - Bahari, Krisna Marta; Fitrisia, Azmi; Ofianto, Ofianto (HK-Publishing, 2022)
AbstractThe Minangkabau community has a very strong traditional philosophy. This philosophy usually explains the way of life and how to socialize with other people. This then led to the emergence of a government system that is also unique to the Minangkabaum community, namely the Nagari government system that follows the Minangkabau traditional philosophy. This research will be conducted with the aim of being able to see how the implementation of the Nagari government in the Minangkabau community, as well as the various factors that influence it. The approach in this study will use a qualitative approach. The data used are obtained from various previous research results which are considered to still have relevance to this study. The results of this study found that there are 3 pillars in the nagari government called